A Model In Vitro Study Using Hypericin: Tumor-Versus Necrosis-Targeting Property and Possible Mechanisms - Yue Li; Shuncong Wang; Yuanyu Zhao; Hexige Saiyin; Xiaoyan He; Juanzhi Zhao; Ling Li; Ali Talebi; Gang Huang; Yicheng Ni (Biology, 2020)
Hypericin (Hyp) had been explored as a tumor-seeking agent for years; however, more recent studies showed its necrosis-avidity rather than cancer-seeking property. To further look into this discrepancy, we conducted an in vitro study on Hyp retention in vital and dead cancerous HepG2 and normal LO2 cell lines by measuring the fluorescence intensity and concentration of Hyp in cells. To question the DNA binding theory for its necrosis-avidity, the subcellular distribution of Hyp was also investigated to explore the possible mechanisms of the necrosis avidity. The fluorescence intensity and concentration are significantly higher in dead cells than those in vital cells, and this difference did not differ between HepG2 and LO2 cell lines. Hyp was taken up in vital cells in the early phase and excreted within hours, whereas it was retained in dead cells for more than two days. Confocal microscopy showed that Hyp selectively accumulated in lysosomes rather than cell membrane or nuclei. Hyp showed a necrosis-avid property rather than cancer-targetability. The long-lasting retention of Hyp in dead cells may be associated with halted energy metabolism and/or binding with certain degraded cellular substrates. Necrosis-avidity of Hyp was confirmed, which may be associated with halted energy metabolism in dead LO2 or HepG2 cells.